Transformative learning theory: A pilot and some implications for human resource training to help NHK furniture company toward sustainable development - Pham, Duc Thieng (Đại học quốc gia Hà Nội, 2020)
It is witnessed that the capacity of labors at small-sized enterprises is generally low for different reasons. Capacity is formed with three factors including attitudes, skills and knowledge, so-called ASK model (Bloom, 1956). Low capacity of labors results in low productivity, high production cost and a low rate of profit, which also means low competitiveness among companies. With such low rate of profit, the company can manage to make a limited investment in human resource development, which remains low capacity of labors. Therefore, the company could escape from this repeated loop as well as improve its competitiveness by increasing investment budget in human resource training. To fulfill this task, it is necessary first for the Director Board to change the irrelevant frames of reference for human resources. In this context, the transformative learning theory developed by Jack Mezirow is considered to be an effective method.